Research on sea surface NB-IoT coverage based on improved SPM - Zheng HU; Baodan CHEN; Jia REN; Yupei FAN; Lian WANG (Tongxin xuebao, 2019)
Based on the standard SPM,an improved sea surface propagation model was proposed.At the same time,a propagation model correction algorithm based on WLS algorithm was proposed.Using the CW test data of Qiongzhou Strait,the parameters of the improved SPM were corrected.Based on the corrected propagation model,the current base station of Qiongzhou Strait coast was used to carry out link level simulation and coverage simulation for NB-IoT.The experimental results show that the proposed method can effectively achieve the coverage of NB-IoT in Qiongzhou Strait and contribute to the scientific research of Internet of things.